2015
DOI: 10.1093/jnci/djv253
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a Biomarker-Based Strategy on Oncology Drug Development: A Meta-analysis of Clinical Trials Leading to FDA Approval

Abstract: Background: In order to ascertain the impact of a biomarker-based (personalized) strategy, we compared outcomes between US Food and Drug Administration (FDA)-approved cancer treatments that were studied with and without such a selection rationale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 40 publications
(62 reference statements)
2
57
0
Order By: Relevance
“…Accumulating evidence suggests that, amongst patients with refractory cancers, a biomarker-based, personalized approach that matches patients with therapies based on specific genomic or protein markers may be able to improve clinical outcome (1014). Herein, we report the genomic alterations identified in 442 patients with CUP using targeted NGS that evaluated ctDNA from patient plasma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that, amongst patients with refractory cancers, a biomarker-based, personalized approach that matches patients with therapies based on specific genomic or protein markers may be able to improve clinical outcome (1014). Herein, we report the genomic alterations identified in 442 patients with CUP using targeted NGS that evaluated ctDNA from patient plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients could potentially be matched to genomically targeted therapy or to immunotherapy or both, as demonstrated by our responding patient who received both a MEK and a checkpoint inhibitor because of the presence of a KRAS and a mismatch repair gene alteration (Figure 4). Previous literature suggests that biomarker-based, matched targeted therapy can improve clinical outcome (1014). Our current report indicates that the non-invasive liquid biopsy approach merits investigation in next generation clinical trials of cancer of unknown primary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested that the matched targeted therapy approach can demonstrate better clinical outcomes than a nonmatched approach, but this implies the need to select patients for the relevant aberration. 3437 Wagner et al 21 showed that responses with MK-8242 (MDM2 inhibitor) were exclusively observed in patients with liposarcoma (RR, 11.1% [three or 27]) whose molecular hallmark includes MDM2 amplification 5 (nonliposarcoma; RR, 0% [zero of 14]). On the other hand, even in a disease such as liposarcoma where > 60% of patients have MDM2 amplification, the RR is relatively low, which may be due to, as mentioned previously, the presence of co-alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in several of the trials using targeted agents alone, response rates were quite low, suggesting the importance of biomarker selection. Indeed, recent large meta-analyses (~70,000 patients) suggest that matched targeted therapy results in improved outcomes, but that targeted therapy without matching often has low or negligible salutary effects [67, 68]. Further, the PFS in phase I trials of mainly matched targeted agents or local therapies in patients with advanced, refractory GBCA and cholangiocarcinoma were similar to that of the first, second, and last-line therapy with FDA-approved agents [3].…”
Section: Overview Of Clinical Trials With Targeted Agentsmentioning
confidence: 99%